Modern approaches to the diagnosis and treatment of cardiac sarcoidosis: results of a cohort study - S. V. Mairina; D. V. Ryzhkova; L. B. Mitrofanova; A. V. Ryzhkov; P. M. Murtazalieva; O. M. Moiseeva (Российский кардиологический журнал)
Aim. To analyze clinical and paraclinical data in patients with documented cardiac sarcoidosis, outlining the key points of diagnosis and selection of the optimal treatment.Material and methods. For the period from 2016 to 2021, 63 patients (50,4±14,1 years) were included in the cohort study on negotiability. Based on a standard examination, 15 patients (41±13 years old) were selected, who continued the examination to confirm the diagnosis of cardiac sarcoidosis. Contrast-enhanced cardiac magnetic resonance imaging (MRI) was performed in 10 patients, while endomyocardial biopsy in 7 patients. All patients underwent 18F-fluorodeoxyglucose positron emission tomography (PET).Results. The most common (53%) electrocardiographic abnormality was right bundle branch block. Ventricular arrhythmias and high-grade atrioventricular block were recorded mainly in patients with documented activity. Regional contractility disorders were predominantly detected in patients with cardiac fibrosis. Delayed contrast enhancement according to cardiac MRI was recorded mainly intramurally in the interventricular septum and subepicardial area of left ventricular (LV) lateral wall. When analyzing the PET results, we found the predominant radiopharmaceutical accumulation in the interventricular septum (56%), lateral (44%) and anterior (33%) LV walls. There was no significant improvement in global LV contractility against the background of immunosuppressive therapy, especially in patients with reduced ejection fraction: initially 49,2±10,1% vs 46,9±14,9% during therapy (p=0,658).Conclusion. A certain apprehensive attitude of the doctor and adherence to the algorithm for early diagnosis of cardiac sarcoidosis allows minimizing the risks of fatal cardiovascular events. On the contrary, in the case of late diagnosis, even the use of aggressive immunosuppressive therapy does not lead to an improvement in global myocardial contractility, and fibrosis zones can cause life-threatening bradyarrhythmias and ventricular arrhythmias.